A banalização da injustiça social no cotidiano de trabalho : a propósito da violência no trabalho e ameaça à saúde do trabalhador - Bila, Neyla Ivanete Gomes de Farias Alves (2008)
Analyzes the factors that unleash violence by banalization of the problems and health questions of workers in a federal public institution, in Natal/RN. It analyzes transformations in the world of the work, with its politic, social and economic determinatives and its relation to the worker health. Boarding the violence in the work enviroment and its implications to the worker health, focusing on the banalization of problems faced by the workers as a kind of violence in and with the work. It was chosen an analitic methodology with qualitative approach, through the collection tecnic and information analyzes according to the thematic oral history, with recorders of authorized personal narratives, through individual interview with a semi-structured guide. In the analyzis of results it were made empiric cathegories: the daily work enviroment and its influence to the worker profession and life; the violence presents in the work enviroment and its consequences to the worker life and health; the banalization of the social injustice, due to violence against the worker that broked their dreams concerned to the nursing contribution. The results revealed the ordinary work of these workers showing enviromental and organizational unhealthy conditions, caracterized by physical and tecnical insecurity; absence and disqualification of instrumental and human supplies; overload and complexity service; bad distribution of the duties and pressure to the deadline and productivity, producing tension, conflict and anxiety related to the users, colleagues, superiors and to the duties. In the work enviroment, it were identified a external violence, caracterized by physical and verbal aggresion, psychic suffering, worker depreciation; and internal, caracterized by: moral and psychological molestations and accupational structural violence. These kinds of violence bring consequences to the life, that is, professional, economic and moral order of factors and to the health by biological, mental and emocional factors. The banalization of social injustice during the daily work was discussed in the aspects of banalization of problems and work conditions, the health, qualification banalizations and professional valorization. The workers expectatives pointed out to the necessity of: secure conditions of work; trainning and tecnical assistance; politics of attention to the physical, mental and social health to the workers and their family. We conclude the enviromental and organizational conditions of the workers interviewed do not offer physical and tecnical security that they need to the execution of their activities, neither offer comfort or physical and psychological satisfactions. The politic the instituition has used points out to the depreciation and inhumanization of them producing feelings as unsatisfaction, frustation and indignation related to the institution and the work, bringing suffering and physical and mental sicking. We noticed the most terrible violence found in the work enviroment is the banalization of social injustice related do the problems and health of these workers, producing a slowly debility and simbolic death of their lifes. Therefore, it is necessary the implementation of a politic that promotes assurance, health and integral education, valorization and humanization of these workers